Marital stability and repartnering: infertility-related stress trajectories of unsuccessful fertility treatment - Martins, Mariana V. (2014)
Objective: To compare the trajectories of infertility-related stress between patients who remain in the same relationship and patients who repartner. Design: Longitudinal cohort study using latent growth modeling. Setting: Fertility centers. Patient(s): Childless men and women evaluated before starting a new cycle of fertility treatment and observed for a 5-year period of unsuccessful treatments. Intervention(s): None. Main Outcome Measure(s): Marital stability and infertility-related stress. Result(s): The majority of patients (86%) remained with their initial partner, but 14% of participants separated and repartnered while pursuing fertility treatments. Marital stability significantly predicted the initial status of infertility stress and infertility stress growth levels. Specifically, patients who repartnered had higher infertility stress levels at all time points compared with those who remained in the same relationship, regardless of the partner they were with at assessment. Furthermore, results showed an increasing stress trajectory over time for those who repartnered, compared with those who remained in a stable relationship. Conclusion(s): Men and women in fertility treatment who form a second union have higher initial levels of stress in their original relationship and higher changes in stress levels over the course of treatments. These findings suggest that high infertility-related stress levels before entering fertility treatment can negatively affect the stability of marital relationships and lead to repartnering.